Wide vessels sustain marginal transpiration flux and do not optimize inefficient gas exchange activity under impaired hydraulic control and salinity. Issue 1 (11th May 2020) - Jerszurki, Daniela; Sperling, Or; Parthasarathi, Theivasigamani; Lichston, Juliana Espada; Yaaran, Adi; Moshelion, Menachem; Rachmilevitch, Shimon; Lazarovitch, Naftali
Abstract : Plants optimize water use and carbon assimilation via transient regulation of stomata resistance and by limiting hydraulic conductivity in a long‐term response of xylem anatomy. We postulated that without effective hydraulic regulation plants would permanently restrain water loss and photosynthetic productivity under salt stress conditions. We compared wild‐type tomatoes to a transgenic type (TT) with impaired stomatal control. Gas exchange activity, biomass, starch content, leaf area and root traits, mineral composition and main stems xylem anatomy and hydraulic conductivity were analyzed in plants exposed to salinities of 1 and 4 dS m −1 over 60 days. As the xylem cannot easily readjust to different environmental conditions, shifts in its anatomy and the permanent effect on plant hydraulic conductivity kept transpiration at lower levels under unstressed conditions and maintained it under salt‐stress, while sustaining higher but inefficient assimilation rates, leading to starch accumulation and decreased plant biomass, leaf and root area and root length. Narrow conduits in unstressed TT plants were related to permanent restrain of hydraulic conductivity and plant transpiration. Under salinity, TT plants followed the atmospheric water demand, sustained similar transpiration rate from unstressed to salt‐stressed conditions and possibly maintained hydraulic integrity, due to likely impaired hydraulic regulation, wider conduits and higher hydraulic conductivity. The accumulation of salts and starch in the TT plants was a strong evidence of salinity tolerance via osmotic regulation, also thought to help to maintain the assimilation rates and transpiration flux under salinity, although it was not translated into higher growth.